Defeat, Entrapment, and Positive Future Thinking: Examining Key Theoretical Predictors of Suicidal Ideation Among Adolescents - Pollak, Olivia H.; Guzmán, Eleonora M.; Shin, Ki Eun; Cha, Christine B. (Frontiers in Psychology, 2021)
Adult-based suicide theories have determined much of what we know about suicidal ideation. Here, we investigate the extent to which elements of the Integrated Motivational-Volitional (IMV) model generalize to adolescence, a period when rates of suicidal ideation increase dramatically. In a sample of community-based adolescents (n = 74), we tested whether defeat and entrapment related to suicidal ideation, and whether poor positive future thinking abilities exacerbated this association. Consistent with the IMV model, we found that defeat/entrapment was associated specifically with history of suicidal ideation, and not with history of suicide attempt. Defeat/entrapment was related to baseline suicidal ideation severity above and beyond depressive symptoms. While defeat/entrapment predicted future suicidal ideation controlling for history of ideation, it did not do so controlling for depressive symptoms. Counter to the IMV model, we initially found that the association between defeat/entrapment and suicidal ideation was strongest among adolescents with greater positive future thinking abilities. This was driven by the tendency to imagine more positive future events, particularly those that are less realistic and achievable. These findings call for a more nuanced understanding of defeat/entrapment and positive future thinking among adolescents, particularly in how they interact to predict recurrent suicidal ideation.